Meningkatkan Keterampilan Komunikasi Efektif dan Pelayanan Prima Bagi Penyedia Layanan Kesehatan: Meningkatkan Keterampilan Komunikasi Efektif dan Pelayanan Prima Bagi Penyedia Layanan Kesehatan - Azizun Kurnia Illahi; Santi Swatikawara; Fitri Hariana Oktaviani (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
In the context of service, implementing effective communication has many advantages, especially when it is applied in the field of healthcare services. Healthcare providers will be able to deliver complete and easily understandable information, helping patients take the next necessary actions. When excellent service and the use of effective communication are successfully implemented, the healthcare center will indirectly build a positive image in the minds of the public. Effective communication itself is the process of successfully exchanging information between two or more parties, where the message delivered is clearly understood, accurate, and has the desired impact. It is also known that effective information transfer requires a strong foundation, which is communication skills. Good communication skills among healthcare providers are considered to have a positive effect on health outcomes and patient satisfaction. These skills are also essential tools for engaging in dialogue with patients to identify issues such as medication usage, treatment effects, or other interactions. Theoretically, the relationship between effective communication and excellent service is twofold, with each influencing the other. However, healthcare services often face challenges related to the provision of services and health information to patients. Therefore, this community service activity is conducted to provide understanding and training on enhancing effective communication skills and service excellence to healthcare workers at primary health centers who provide services to patients or accompany them.